Thermo-stabilized, porous polyimide microspheres prepared from nanosized SiO2 templating via in situ polymerization - M. Q. Liu; J. P. Duan; X. Z. Shi; J. J. Lu; W. Huang (eXPRESS Polymer Letters, 2015)
In this article, we addressed a feasible and versatile method of the fabrication of porous polyimide microspheres presenting excellent heat resistance. The preparation process consisted of two steps. Firstly, a novel polyimide/nano-silica composite microsphere was prepared via the self-assembly structures of poly(amic acid) (PAA, precursor of PI)/nanosized SiO2 blends after in situ polymerization, following the two-steps imidization. Subsequently, the encapsulated nanoparticles were etched away by hydrofluoric acid treatment, giving rise to the pores. It is found the composite structure of PI/SiO2 is a precondition of the formation of nanoporous structures, furthermore, the morphology of the resultant pore could be relatively tuned by changing the content and initial morphology of silica nano-particles trapped into PI matrix. The thermal properties of the synthesized PI porous spheres were studied, indicating that the introduction of nanopores could not effectively influence the thermal stabilities of PI microspheres. Moreover, the fabrication technique described here may be extended to other porous polymer systems.